(untitled) (Res Medica, 2014)
It was the introduction of ether by Morton in 1846 that provided the necessary conditions for the development of Modern Surgical practice. Previous to its use Surgery was swift and brutal, its scope confined to the body surface, i.e. the evacuation of pus, amputation of limbs, excision of superficial tumours. It is revealing to examine the operations performed in the Royal Infirmary, Edinburgh, in the years 1831-34, a total of one hundred and forty, an average of thirty-five a year. Hovell remarks, “Although in 1829 the staff of the Royal Infirmary included surgeons of great reputation, very few operations were performed, and the operation theatre served little purpose.” It is hard today to realise the impact of the new discovery on the medical profession, yet in a very short time ether was to be supplanted by chloroform. I have often wondered why this happened. History is rather vague on this point. The major objection appears to have been its unpleasant smell. I suspect there were other reasons. The entrepreneurs of the time, realising the importance of the event, were anxious to participate in it. A frantic search for new drugs began and in November 1847 Simpson of Edinburgh used chloroform, first in obstetrics and then nearly six months later in general surgery.